"What would you recommend doctor?"—Discourse analysis of a moment of dissonance when sharing decisions in clinical consultations. (27th March 2019) - Sherlock, Rebecca; Wood, Fiona; Joseph‐Williams, Natalie; Williams, Denitza; Hyam, Joanna; Sweetland, Helen; McGarrigle, Helen; Edwards, Adrian
Abstract: Background: Proven benefits of Shared Decision Making (SDM) include improved patient knowledge, involvement and confidence in making decisions. Although widely advocated in policy, SDM is still not widely implemented in practice. A common patient‐reported barrier is feeling that "doctor knows best"; thus, patients often defer decisions to the clinician. Objective: To examine the nature of the discourse when patients ask clinicians for a treatment recommendation during consultations when treatment decisions are being shared and to examine clinicians' strategies used in response. Design, Setting and Participants: Theme‐orientated discourse analysis was performed on eight audio‐recordings of breast cancer diagnostic consultations in which patients or their partners attempted to defer treatment decisions to the clinician. Clinicians were trained in SDM. Results: Tension was evident in a number of consultations when treatment recommendations were requested. Clinicians responded to recommendation requests by explaining why the decision was being shared (personal nature of the decision, individual preferences and equivalent survival outcomes of treatment options). There was only one instance where a clinician gave a treatment recommendation. Discussion and Conclusions: Strategies for clinicians to facilitate SDM when patients seem to defer decisional responsibility include being clear about why the decision is being shared, acknowledging that this is difficult and making patients feel supported. When patients seek guidance, clinicians can provide a recommendation if grounded in an understanding of the patient's values.